2006
DOI: 10.1158/0008-5472.can-06-1766
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M (OSM) Cytostasis of Breast Tumor Cells: Characterization of an OSM Receptor β–Specific Kernel

Abstract: The interleukin-6 cytokine oncostatin M (OSM) induces potent growth-inhibitory and morphogenic responses in several different tumor cell types, highlighting the importance of OSM signaling mechanisms as targets for therapeutic intervention. The specific molecular pathways involved are not well understood, as OSM can signal through two separate heterodimeric receptor complexes, glycoprotein 130 (gp130)/leukemia inhibitory factor receptor (LIFR) A and gp130/OSM receptor B (OSMRB). In this investigation, we used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…This effect was associated with the activation of cytokine gene expression, suggesting that these cytokines may be involved in the P245-mediated inhibition of tumour growth (Pagliacci et al, 1993;Derynck et al, 2001;Shen et al, 2002;Underhill-Day and Heath, 2006). Interestingly, inhibition of breast cancer stem cells by TGF-b1 was reported recently (Tang et al, 2007) and TGF-b1 signalling is functional in CD44 þ breast cancer cells (Derynck et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…This effect was associated with the activation of cytokine gene expression, suggesting that these cytokines may be involved in the P245-mediated inhibition of tumour growth (Pagliacci et al, 1993;Derynck et al, 2001;Shen et al, 2002;Underhill-Day and Heath, 2006). Interestingly, inhibition of breast cancer stem cells by TGF-b1 was reported recently (Tang et al, 2007) and TGF-b1 signalling is functional in CD44 þ breast cancer cells (Derynck et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…19 OSM activates a gp130/ OSMRb receptor (OSMR) protein complex that is distinct from other IL-6 family co-receptors, which may account for the more potent OSM-induced senescence response. 26,76,77 OSMR complexes consisting of gp130/OSMRb heterodimers can activate STAT3, RAS-MAPK, and PI3K-AKT signaling, in addition to pathways not activated by other IL-6 family receptor complexes that signal via gp130/gp130 homodimers (STAT5, STAT6, AKT, and PKC-d). 19 In order to bypass the senescence program, developing cancer cells must dismantle cell cycle control by either inhibiting p16, pRb, and p53 or activating MYC (c-MYC).…”
Section: Discussionmentioning
confidence: 99%
“…22,25 Whereas OSM drives proliferation, epithelial-mesenchymal transition (EMT), invasion, and metastasis in breast cancer cells and transformed human mammary epithelial cells (HMEC), it engages senescence in normal and non-transformed HMEC. 13,[19][20][21][26][27][28][29][30][31][32][33][34] Senescence is an irreversible, proliferationinhibiting response that occurs in 2 steps: 1) reversible cell cycle arrest followed by 2) futile growth-induced gerogenic conversion, or geroconversion. [35][36][37] Moreover, senescence is a major tumorsuppressive mechanism that acts as an early barrier to thwart cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…It was first identified as a secreted product of macrophage-like cells that inhibited proliferation of melanoma-, neuroblastoma-, and lung cancer-derived cell lines (2), and although it suppresses breast cancer cell proliferation (3), it has been suggested to support metastasis of breast cancer in the skeleton due to proosteoclastic activities (4) and to stimulate Kaposi's sarcoma (5). Studies in knock-out mice have shown that OSM supports hematopoiesis (6) and bone formation at the expense of adipogenesis (7), but it has also been implicated in pulmonary tissue fibrosis (8), cardiac disease and repair (9), prostate cancer (10), asthma (11), periodontal disease (12), and both rheumatoid and osteoarthritis (13).…”
Section: Oncostatin M (Osm)mentioning
confidence: 99%